O DIÁLOGO E A PROBLEMATIZAÇÃO: APORTES PEDAGÓGICOS PARA A FORMAÇÃO CONTINUADA - Claudia Pereira de Pádua Sabia; Cláudio Roberto Brocanelli; Camila Godoy Paredes (Universidade do Oeste Paulista, 2015)
Many searches are conducted by scholars motivated to identify issues that will most affect the national educational system. Within this context issues related to methodology, school infrastructure, public policy and equal opportunity are raised constantly, but it is essential investigate deeper causes that directly influence teaching and learning. Through action research identified gaps left by the initial training of teachers and educational managers and the need to contribute to their training, enabling a more meaningful and qualified practice. The central aim of this study is to demonstrate the importance of continuing education, and present the "Dialogue and the Problematization" proposal with public schools that is in progress. The research is being developed in a qualitative approach and data collection. The methodology used is the literature search. As results will point out possibilities of transformation of pedagogical practice fostered by continuous training of educators.